ChemInform Abstract: Different Products in the Reaction of the Alcohols with Cyclic and Acyclic 1, 3‐Dicarbonyl Compounds: K5CoW12O40 as an Electron Transfer Nano Catalyst. Issue 18 (11th April 2013) - Rafiee, Ezzat; Kahrizi, Masoud; Joshaghani, Mohammad
Abstract The reactions of linear 1, 3‐dicarbonyl compounds with alcohols afford C‐alkylation products (III), whereas O‐alkylation takes place in the case of cyclic diketone (IV).